(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This study proposes a comprehensive methodological framework for enhancing the capital value of joint-stock companies, emphasizing the integration of good corporate governance principles. The research develops a conceptual and empirical model that incorporates key governance tools such as independent directorship, strategic openness, dividend policy, and corporate social responsibility. The model is tested using data from joint-stock companies in Uzbekistan and comparator countries. The findings indicate a strong correlation between good governance practices and increased market value. Based on these insights, the study provides concrete institutional, regulatory, and managerial recommendations aligned with sustainable development goals (SDGs).